Roles of fibrin α- and γ-chain specific cross-linking by FXIIIa in fibrin structure and function - Duval, Cédric; Allan, Peter; Connell, Simon D. A.; Ridger, Victoria C.; Philippou, Helen; Ariëns, Robert A. S. (Thrombosis and Haemostasis, 2014)
Factor XIII is responsible for the cross-linking of fibrin γ-chains in the early stages of clot formation, whilst α-chain cross-linking occurs at a slower rate. Although γ- and α-chain cross-linking was previously shown to contribute to clot stiffness, the role of cross-linking of both chains in determining clot structure is currently unknown. Therefore, the aim of this study was to determine the role of individual α- and γ-chain cross-linking during clot formation, and its effects on clot structure. We made use of a recombinant fibrinogen (γQ398N/Q399N/K406R), which does not allow for y-chain cross-linking. In the absence of cross-linking, intact D-D interface was shown to play a potential role in fibre appearance time, clot stiffness and elasticity. Cross-linking of the fibrin α-chain played a role in the thickening of the fibrin fibres over time, and decreased lysis rate in the absence of α2-antiplasmin. We also showed that α-chain cross-linking played a role in the timing of fibre appearance, straightening fibres, increasing clot stiffness and reducing clot deformation. Cross-linking of the γ-chain played a role in fibrin fibre appearance time and fibre density. Our results show that α- and γ-chain cross-linking play independent and specific roles in fibrin clot formation and structure.
Keywords: Fibrinogen; factor XIII; clot structure